Selection of a mathematical model through the AHP methodology to model green roofs in Colombia (2018)
Green roofs (GR) are engineering structures that stores rainwater as an alternative for urban stormwater management. This research is carried out to select a mathematical model to simulate the experimental TV dynamics from Bogotá, improving the decision-making process regarding GR real implementation in intertropical urban areas of Colombia that considers meteorological, substrate and design variables. A hierarchical analytical method (AHP) is used to select the model for simulating GR. The AHP is a matrix technique that allows a decision-making process based on expert criteria in order to decrease the bias of subjectivity during the assessment. First, a bibliographic review is made to identify GR models to be evaluated: SWAM, SWMM 5.1, HYDRUS 1-D, SWAP, SWMS 2-D, MIKE URBAN, WinSLAMM and SUSTAIN. Then, each model performance is qualified with respect to the selection criteria (Input data, attributes, and output). The value judgments issued by the experts are used to develop paired matrices with the AHP methodology to obtain the model that best meets the selection criteria. The model EPA-SWMM 5.1 is found to comply with the proposed requirements for modeling GR in Colombia. SWMM is a free software that has a SUDS module and allows continuous events simulation, among other variables. A hierarchical list is developed for other modeling user ́s decision according to their GR modeling needs.